The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1530/eje-10-0307
|View full text |Cite
|
Sign up to set email alerts
|

Low testosterone levels predict all-cause mortality and cardiovascular events in women: a prospective cohort study in German primary care patients

Abstract: Objective: Although associations between testosterone and cardiovascular (CV) morbidity in women have been proposed, no large prospective study has evaluated potential associations between testosterone and mortality in women. The objective was to determine whether baseline testosterone levels in women are associated with future overall or CV morbidity and mortality. Design: Prospective cohort study with a 4.5-year follow-up period. Methods: From a representative sample of German primary care practices, 2914 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 35 publications
7
77
4
Order By: Relevance
“…Sievers et al (2010) reported that low baseline testosterone in relatively older women is associated with increased all-cause mortality and cardiovascular events, which is largely independent of traditional risk factors. Low-dose testosterone supplementation improved functional capacity, insulin sensitivity and muscle strength in elderly female patients with chronic heart failure, and no androgenic side effects were detected (Iellamo et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Sievers et al (2010) reported that low baseline testosterone in relatively older women is associated with increased all-cause mortality and cardiovascular events, which is largely independent of traditional risk factors. Low-dose testosterone supplementation improved functional capacity, insulin sensitivity and muscle strength in elderly female patients with chronic heart failure, and no androgenic side effects were detected (Iellamo et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore possible that more recent studies may have greater power to detect an association between sex steroid levels and ischemic CVD risk. In support of this possibility, more recent prospective cohort studies [5,6,17,19,21,24,28] have tended to report the presence of significant relationships between endogenous sex steroids and ischemic CVD risk.…”
Section: Issues Of Measurementmentioning
confidence: 99%
“…Elevated testosterone levels and low levels of sex hormone-binding globulin have been found to be positively associated with CV risk factors and the metabolic syndrome in postmenopausal women [3,4]. However, others have reported an increased CV morbidity and mortality in postmenopausal women with low testosterone levels [5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…In premenopausal women, hyperandrogenism, such as is present in polycystic ovary syndrome, is associated with adverse metabolic effects. In postmenopausal women, however, various studies have reported conflicting results in CV outcomes in association with high- as well as low-circulating testosterone levels [3,4,5,6]. …”
Section: Introductionmentioning
confidence: 99%